POLYGAMIC POLICY IN INDONESIA (Analysis of Polygamic Arrangements and Practices 1959-2015) - Warman Warman; Gunarto Gunarto; Akhmad Khisni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In essence, marriage is a sense of love, obligation, the fulfillment of sexual desire and resuming the descent. In Islam, a sense of love is the first pillar of a marriage. One principle of marriage is monogamy principle, where a man can have only one wife and vice versa (in time). Monogamy principle here is open or not absolute. These properties are not absolute monogamy principle set forth in article 2, paragraph 2, 4 and 5 of paragraph (1) of Law No. 1 of 1974 concerning marriage and regulated in article 55, paragraph 56 (1), 57 Compilation of Islamic Law; in fact, regulated, also in the Koran, that Q.S. An-Nissa paragraph 3. The term of polygamy itself is a term that is often present in everyday life. The term polygamy has a close relationship with marriage, both in new families and families who have been doing weddings Formulation of the problems discussed in this dissertation as follows: 1) How does the construction of polygamy laws and procedures set out in the legislation in Indonesia since the year 1959 to 2015? 2) How does the practice of polygamy since 1959-2015? 3) How is the reconstruction of polygamy ideal setting in the future? The method used in this research is using socio legal reserch method or can be called a sociological juridical approach. Constructivism paradigm is the paradigm of a social reality where truth is seen as socially constructed, and the truth of a social reality is relative. The results of this study were 1) the provisions laid down concerning the setting of polygamy in Indonesia as the basis of the implementation of polygamous marriage contained in the Act No. 1 Year 1974 on Marriage, KHI and government regulation No. 9 of 1975 concerning the Implementing Regulations of Law No. 1 Year 1974 on Marriage, then it is very optimistic and believes that the prospect of polygamy is getting better, and opens the possibility of polygamy for highly skilled and have a sincere intention for happiness and prosperity. 2) The debate is getting better when the draft law on marriage proposed to become law. Finally, after a long debate, monogamous finally set to be one of the principles but with an exception for people who are under the law and allowed to take more of a religion. 3) The doctrine of polygamy after the entry of the Prophet Muhammad and Islam became more orderly and has provisions in its implementation. A husband and wife have a maximum of only limited amounts to four people with the terms and conditions when it is able to be fair and able to provide maintenance to his wives. If a husband is not able to be fair and not be able to give birth to a living wives then it is better for a man married is only one person. Keywords: Polygamy, Polygamy Rules, Practice Polygamy in Indonesia